Observer-based fault diagnosis for trucks belt tensioner. Issue 1 (July 2017) - Dubuc, Donatien; Sename, Olivier; Bresch-Pietri, Delphine; Gauthier, Christophe
Abstract: This paper deals with the monitoring of a serpentine belt tensioner performance, a critical automotive engine component guaranteeing the cooling system efficiency. A belt tensioner fault will affect the transmission, deteriorate the water pump efficiency, and eventually, lead the engine to stall. Monitoring this component is thus a key to design predictive or corrective maintenance. In this paper, we propose to estimate a parameter which is shown to be characteristic of this component's health by using an Adaptive Observer or an Extended Kalman Filter. Respective merits of these solutions are compared using simulations performed with GT-SUITE on a high-fidelity model.